The Typology of the Traditional Detective Fiction in Doyle’s A Study in Scarlet and the chronotopic variation that accounts for the generation of new genres: Twain’s A Double Barrelled Detective Story and Chandler’s Killer in the Rain. - Bottai, Sabrina Cecilia Noemí (2021)
Fil: Bottai, Sabrina Cecilia Noemí. Universidad Nacional del Litoral. Facultad de Humanidades y Ciencias; Argentina.